Research on Driver Driving Behavior Based on Decision Tree - LI Xi; FENG Ba; XIE Yongbo; WANG Wenming (Kongzhi Yu Xinxi Jishu)
Driver driving behavior is one of the important factors affecting energy consumption of vehicle. In order to accurately analyze driving behavior of a driver, correlation analysis of driving behavior parameters through grey correlation analysis was made, and then a driver driving behavior model was established combined with C4.5 decision tree algorithm. Finally, actual operation data were used to train and test. The results show that with the model the driving behavior of a driver can be accurately analyzed and this can provide an effective basis for driving behavior analyzing.